2015
DOI: 10.1161/atvbaha.114.304649
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines Control Mobilization, Recruitment, and Fate of Monocytes in Atherosclerosis

Abstract: Abstract-Atherosclerosis is a chronic inflammatory disease of large arteries and, among others, characterized by continuous influx of monocytes into the subendothelial space, subsequent macrophage accumulation, and foam cell formation. Chemokines and their receptors tightly orchestrate monocyte trafficking and fate from birth to death. This brief review summarizes our current understanding of the interplay between monocytes and chemokines entertaining crucial processes in atherosclerosis development, progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…10 Arterial macrophage accumulation is controlled by different mechanisms, including apoptosis, recruitment, and proliferation. 11 In previous work, it has been shown that AnxA1 and its N-terminal fragment Ac2-26 counteract chemokine-induced integrin activation by inhibition of Rap1 activation in monocytes and, therefore, restrains adhesion to large arteries. 5 Consequently, enhanced recruitment of monocytes in AnxA1-deficient mice may contribute to the phenotype observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…10 Arterial macrophage accumulation is controlled by different mechanisms, including apoptosis, recruitment, and proliferation. 11 In previous work, it has been shown that AnxA1 and its N-terminal fragment Ac2-26 counteract chemokine-induced integrin activation by inhibition of Rap1 activation in monocytes and, therefore, restrains adhesion to large arteries. 5 Consequently, enhanced recruitment of monocytes in AnxA1-deficient mice may contribute to the phenotype observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…4,83,84 At the beginning of atherosclerosis, monocytes, which are attracted by the chemokines secreted by resident vascular cells, migrate into the subendothelial area where they differentiate into macrophages on growth factors stimulation. 83 In the atherosclerotic lesions, macrophages ingest oxidized LDL through scavenger receptors and become lipid-laden foam cells.…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…[1][2][3] An inflamed endothelium recruits inflammatory cells, such as monocytes, via the expression of various mediators and chemokines. [4][5][6] This, in addition to the accumulation of cholesterol and smooth muscle cells (SMCs) in the intima, leads to the transformation of monocytes into foam cells, which consume dead cells and lipids. [7][8][9] The atherogenic process involves multiple cell types, that is, endothelial cells (ECs), 10 SMCs, 11 immune cells, 12 and stem/progenitor cells, 13 in which levels of both intracellular and extracellular reactive oxygen and nitrogen species play a fundamental role in vascular cell homoeostasis and eventually affects the development of atherosclerosis.…”
mentioning
confidence: 99%
“…Furthermore, CXCL1/CXCR2 signaling also contributes to blood monocytosis. In mice fed a highcholesterol diet, CXCL1 neutralization dampens expansion of blood Ly6C high monocytes (31).…”
Section: Bm Monocyte Releasementioning
confidence: 99%